Hyperhydration using different hydration agents does not affect the haematological markers of the athlete biological passport in euhydrated volunteers - Athanasiadou, I.; Voss, S. C.; El Saftawy, W.; Al-Maadheed, M.; Valsami, G.; Georgakopoulos, C. (Journal of Sports Sciences, 2020)
Athlete Biological Passport (ABP) is an indirect approach, implemented by WADA, aimed at detecting blood manipulation based on abnormal changes in haematological markers. Cases report the use of hyperhydration as masking method during anti-doping urine sample collection which could potentially mask suspicious fluctuations on ABP profiles. This study investigated the hyperhydration effect on haemoglobin concentration, reticulocyte percentage and OFF-hr score (an algorithm based on haemoglobin concentration and reticulocyte percentage), with and without recombinant human erythropoietin (rHuEPO) administration. A five-week clinical study performed; Baseline and rHuEPO Phase. Water and a sports drink were used as hyperhydration agents. To examine the hyperhydration effect on the normal ABP profile per volunteer, hyperhydration was implemented at 0, 24 and 48 hours during the baseline. During the rHuEPO phase, volunteers received Epoetin beta (3000 IU) with hyperhydration to be implemented at 0, 24 and 48 hours after drug administration. Blood and urine samples were collected and analysed according to WADA guidelines. No significant effect on ABP markers was observed due to hyperhydration at any time during the study. Pre- and post-hyperhydration data were not statistically different compared to individual baseline data. In conclusion, hyperhydration does not affect the ABP haematological markers under the examined conditions.